Deposição de nano-grãos de Co em uma matriz de CoO/Al2O3 por Magnetron Sputtering - Gomes, Matheus Gamino (2007)
Granular magnetic systems can be composed by magnetic particles or clusters with size of some nanometers. These magnetic nanoparticles present different magnetic order phases, as superparamagnetic, and they can be embedded in both, metallic or insulating matrix. These systems present several phenomena such as the giant magnetoresistance (GMR), tunnel magnetoresistance (TMR) and Coulomb blockade. That phenomena use to disappear when a small termal fluctuation is high enough to reverse the magnetization of the clusters leading the lost the magnetic information in a very short time range. When it occurs, the nano-particles are in superparamagnetic phase. In order to maintain the magnetic information at high values of temperature, or even to suppress the superparamagnetic limit, many works have tried to use an antiferromagnetic matrix, to induce the increase of the energy barrier among the two directions of magnetization easy by the exchange coupling in the grain(FM)/matrix(AFM) interfaces, with the purpose of stabilizing the nano-particles magnetization. In this work, we have produced Co granular samples inside an Al2O3/CoO insulating/antifferomagnetic matrix through a sequential deposition by magnetron sputtering. We aim to explore the couplingmechanisms among the ferromagnetic nanoparticles and the antiferromagnetic matrix. It has been performed measurements of Impedance Spectroscopy (IS), X-ray Difraction (XRD), and magnetization at function temperature analysed by zero-field cooling/field cooling curves (ZFC-FC) at some samples in order to obtain information about the magnetic and structural properties. The measurements of IS and XRD corroborate the formation of Co clusters and the magnetization versus temperature curves to some samples do not indicate evidence of the exchange coupling among the Co clusters and the CoO antiferromagnetic matrix.